MANAJEMEN PEMASARAN DALAM ORGANISASI - Rindu Rodiah; Ayu Hijrani, Faiz Nayla, Dini Vientiany (CV. Adiba Aisha Amira, 2024)
This research aims to explore the role and impact of marketing management in organizations. In an era of intense business competition, marketing management is one of the keys to success for organizations in achieving their strategic goals. The research method used is a qualitative method with a literature study approach, which includes analysis of literature, scientific journals and case studies related to marketing management. The research results show that effective marketing management plays an important role in increasing brand visibility, influencing consumer perceptions, and increasing sales and profits. Some marketing strategies that have proven to be effective include appropriate market segmentation, innovative product development, competitive pricing, efficient distribution, and creative and sustainable promotions. In addition, this research also found that the integration of digital technology in marketing, such as the use of social media and data analysis, has a significant positive impact on an organization's marketing performance. Obstacles faced in implementing marketing management include budget limitations, rapid changes in consumer preferences, and intense competition. This research confirms that strategic and adaptive marketing management is very important for organizations to achieve competitive advantage and business sustainability. Recommendations for further research include more in-depth empirical studies of the effectiveness of digital marketing strategies and their impact on various types of industries.